DIABETES MELLITUS IN WOLFRAM SYNDROME 1: CHARACTERISTICS AND PERSPECTIVES IN TREATMENT - Darasz, Dominika; Zając, Dominik; Łobaziewicz, Marek; Powaga, Patrycja; Sęk, Michał; Wajs, Aleksandra; Gródek, Aleksandra; Kierner, Julia; Valipur Kolti, Daria; Żurek, Amelia (International Journal of Innovative Technologies in Social Science, 2026)
Wolfram syndrome 1 is a rare autosomal recessive disorder caused by mutations in the WFS1 gene related to endoplasmic reticulum (ER) function. The course of the disease most often begins with diagnosis of insulin-dependent non-autoimmune diabetes mellitus with an early onset. Its clinical character is presented with an acronym DIDMOAD: diabetes insipidus (DI), diabetes mellitus (DM), optic atrophy (OA) and deafness (D).This article focuses on the clinical features of diabetes mellitus in Wolfram syndrome. We also describe current approach to its therapy and discuss possible treatment options placing the main emphasis on the GLP1 receptor agonists and cell regenerative therapy.Methods and materials: A qualitative synthesis of the data focusing on GLP-1 agonists, cell regenerative therapy and diabetes mellitus in Wolfram syndrome was performed. This literature review of GLP-1 receptor agonists and cell regenerative therapy effect on metabolic control, and current perspectives of treatment in patients with Wolfram syndrome, a monogenic type of diabetes, included recent publications, primarily from the past 10 years, and was conducted from November 2025 to April 2026 using the PubMed database.A systematic search was performed using specific keywords and medical subject headings (MeSH terms) related to GLP-1 agonists and Wolfram syndrome. The primary search terms included: “diabetes mellitus”, “GLP-1 agonists”, “Wolfram syndrome”, “WFS1”, “monogenic diabetes”, “islet transplantation”, and “cell regenerative therapy”. The criteria for inclusion of articles were as follows: published before April 2026, written in English, peer-reviewed original research articles. Exclusion criteria included publications not available in full text, articles in languages other than English. Editorials, commentaries, and conference abstracts without full data were also excluded. Titles and abstracts of the retrieved articles were screened to determine eligibility based on the inclusion and exclusion criteria.